Formulasi dan Analisis Nilai Gizi Biskuit Mocaf (Modified Cassava Flour), Kelor, Ikan Lemuru sebagai Pangan Fungsional Sumber Protein, Zat Besi dan Omega-3 - Anggraeni, Siti Lutfiah; Utami, Arfiati Ulfa; Setyawan, Bagus; Kurnia, Tristi Indah Dwi (Agricultural Technology Education Study Program, 2025)
Stunting remains a major public health problem in Indonesia, primarily caused by chronic nutritional deficiencies during the first 1,000 days of life. The development of functional foods rich in protein, essential fatty acids, calcium, and iron can help meet the nutritional needs of mothers and children. This study aimed to evaluate the nutritional composition of cookies made from mocaf flour, moringa leaf flour, and lemuru fish flour as a functional food to support the nutritional requirements of pregnant women in efforts to prevent stunting. A Completely Randomized Design (CRD) was used with four treatments, namely P0 (100% mocaf), P1 (82% mocaf, 15% moringa, 3% lemuru), P2 (75% mocaf, 20% moringa, 5% lemuru), and P3 (68% mocaf, 25% moringa, 7% lemuru), each repeated four times. The analyzed parameters included protein, fat, calcium, iron, and omega-3 fatty acids. Increasing the substitution of moringa and lemuru flours significantly enhanced the nutritional content of the cookies (p < 0.05), including protein, fat, calcium, iron, and omega-3 levels. The best formulation was obtained from cookies composed of 68% mocaf, 25% moringa leaf flour, and 7% lemuru fish flour (P3). This formulation contained 12.28% protein, 28.15% fat, 412.12 mg calcium, 2.99 mg iron, and 320.67 mg omega-3 per 100 g. The results of this study provide valuable insight into the utilization of mocaf, moringa leaves, and lemuru fish to support the nutritional needs of pregnant women and help reduce stunting prevalence in Indonesia.